¿Listening to science? A proposal of historical periodization of the problem of climate change communication - Mateos Martín, Concha (2025)
This article reviews the evolution of the problem of climate change science communication from 1988 to 2022 to determine the current state of the question and to identify the rhetorical approaches most widely used to date. Methodologically, a distinction is first drawn between institutional milestones and rhetorical moments in discourses originating in science, politics, and the arts/media. A general corpus of 13,794 documents, including scientific literature, journalistic sources, and official reports, is then reviewed. The result is a proposal for a historical periodization with three periods: from 1988 to 2009, characterized by pragmatic communication needs; from 2010 to 2015, when the need to communicate climate change as a social fact emerged; and from 2016 to 2022 when climate change began to elicit specific political action on the international stage. The results reveal evidence of rhetorical connections in the discourses used by the different actors involved in socially shaping public knowledge of climate change. As to the conclusions, it is essential to explore hybrid formulas of epistemic authority and to conduct further research on a dialogic model of science communication that does not overlook the need to “listen to science”, while also including the idea of a science that listens.